Effects of Farmers or Herders Conflict on Food Security in Benue State - Dominic Aondona Iornumbe (Jurnal Restorasi : Hukum dan Politik, 2025)
Increase in herds number, due to improved conditions of the cattle, compels the pastoralists to look for more pastures to feed the cattle. Also, improvements in human health due to better health services, increase human population who depend on food crops for survival. These imply that both the farmers and the pastoralists engage in fierce struggles for access to available arable land for cultivation and grazing that lead to conflicts. The intensity and variations of the conflicts depend on the nature and type of the user groups where the herdsmen graze their cattle. Many times, attempts by farmers to prevent them from causing havoc are met with stiff and violent resistance. Most times, the farmers are overpowered, injured, killed while others are evicted from their homes. Sometimes, the herdsmen are accused of taking the opportunities to steal, raze houses, rape women and other innocent citizens are killed. The conflicts constitute serious threats to means of livelihood, food production, lives, property and development. The Fulani constitute the major owners and breeders of cattle that provide the main source of animal proteins and meat in Nigeria. The Fulani own over 90% of the nation's livestock population. The herdsmen and farmers crisis in Nigeria has gained significant attention due to its socio-economic and political implications. Scholars have extensively studied the conflict, offering diverse perspectives on its causes and consequences. For instance) argue that the crisis stems from competition for scarce resources such as land and water. The research adopted research needs theory. Secondary data were used.